Regulatory T cells inhibit autoantigen-specific CD4+ T cell responses in lupus-prone NZB/W F1 mice - Rosenberger, Stefan; Undeutsch, Reinmar; Akbarzadeh, Reza; Ohmes, Justus; Enghard, Philipp; Riemekasten, Gabriela; Humrich, Jens Y. (Frontiers in Immunology, 2023)
Progressive loss of regulatory T cell (Treg)-mediated control over autoreactive effector T cells contributes to the development of systemic lupus erythematosus (SLE). Accordingly, we hypothesized that Treg may also have the capacity to suppress the activation of autoreactive CD4 + T cells that are considered to drive autoimmunity. To investigate whether Treg are involved in the control of autoreactive CD4 + T cells, we depleted CD25 + Treg cells either in vivo or in vitro, or combined both approaches before antigen-specific stimulation with the SLEassociated autoantigen SmD1(83-119) in the NZB/W F1 mouse model either after immunization against SmD1(83-119) or during spontaneous disease development.Frequencies of autoantigen-specific CD4 + T cells were determined by flow cytometry using the activation marker CD154. Both in vitro and in vivo depletion of CD25 + Treg, respectively, increased the frequencies of detectable autoantigen-specific CD4 + T cells by approximately 50%. Notably, the combined in vivo and in vitro depletion of CD25 + Treg cells led almost to a doubling in their frequencies. These results suggest that the activation and expansion of autoantigen-specific CD4 + T cells are partly controlled by Treg in murine lupus. Depletion of Treg therefore can be a useful approach to increase the detectability of autoantigen-specific CD4 + T cells allowing their detailed characterization and sufficient ex vivo isolation.